Synthesizing and characterization of nano-Graphene Oxide-reinforced Hydroxyapatite Coatings on laser treated Ti6Al4V surfaces - Bulbul, Ertugrul; Aksakal, Bunyamin (WROCLAW UNIV TECHNOLOGY, 2017)
Laser-treated Ti6Al4V surfaces were coated by the single-layer hydroxyapatite (HA) and double-layer hydroxyapatite reinforced by the reduced nano-graphene oxide (rGO) using the sol-gel method. The effects of rGO reinforcement at different ratios and sintering temperatures on surface morphology and adhesion strength of the single and double layer coatings (rGO/HA) were analysed. As the initial treatment process, a laser texturing was patterned on the alloy and then, prepared samples were coated. The coated laser-modified HA and HA/rGO-coated Ti6Al4V surfaces were characterized by Raman spectroscopy, X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and the adhesion strength between the coat and substrates were determined by the standard adhesion tests. The conducted analyses indicated that the substitution of rGO into HA matrix revealed a homogeneous morphology and relatively crack-free coatings on the laser-treated Ti substrate surfaces. Adhesion tests showed that, the HA + rGO (1.0 wt. %) biocomposites exhibited a significant increase in adhesion strength compared to untreated surfaces and to the single HA-coated Ti6Al4V substrates.
Keywords: surface treatment; hydroxyapatite; nano-graphene oxide; sol-gel; MECHANICAL-PROPERTIES; BIOMEDICAL APPLICATIONS; COMPOSITES; BIOCOMPATIBILITY; NANOCOMPOSITES; Biophysics; Engineering